Petrographic and Size Analysis of Lithic Artifacts of Loreto (Early Middle Pleistocene, Basilicata, Italy) to Support Insight on the Site Lithic Industry and Human Behavior - Giacomo Eramo; Giovanna Fioretti; Jacopo Conforti; Marco Carpentieri; Marie-Hélène Moncel (Heritage, 2025)
The Lower Paleolithic site of Loreto (Venosa Basin, Basilicata, Southern Italy), discovered in 1929 and excavated from 1956 to 1961 and from 1974 to 1981, consists of three main archaeological layers showing evidence of human occupation. The bottom layer (Layer A) is the richest and best-preserved layer, and its lithic industry includes flakes, retouched flakes, cores, and pebble tools mainly made of chert and limestone. This study involves the petrographic and morphometric analysis of about 400 artifacts. A comparison with the geological clasts of Layer B of the archaeological site of Notarchirico (Venosa), as well as geological samples from the outer tectonic units of the Southern Apennines chain available in the SiLiBA lithotheque and analyzed with the same methodological approach, provided not only the identification of the lithotypes and their source formations but also allowed for insights into technological behavior and human–environment interaction.